HUBUNGAN PENJADWALAN KERJA DENGAN KELELAHAN KERJA PERAWAT RUANG RAWAT INAP DI MASA PANDEMI (COVID-19) - Manesin, Nora Rosa Cornelia Eka Putri; Zunaedi, Rosly; Ramadhani, Rahmaniah (Jurnal Ilmiah Kesehatan Media Husada, 2024)
Work fatigue is still a problem in the world of work. This is shown by the data in which work fatigue is a factor that contributesas much as 50% or more to the occurrence of work accidents. The work schedule plays an important role in a person's sleepdisorders, physical and psychological disorders as well as social and family disorders. Objective to examine the correlationbetween nurses scheduling and work fatique in inpatient room during a pandemic (COVID-19). Method This study used ananalytical survey design by using the retrospective approach. The sampling technique in this study was probability samplingby using simple random sampling. Instruments were the form of a questionnaire of evaluation of nursing service schedulingin inpatient rooms and IFRC (Industrial Fatigue Research Committee). The number of respondents was 73 nurses. Thestatistical test used was the Somers'd test to determine the correlation between variables of work scheduling and work fatigueof inpatient nurses. Results out of 73 respondents, the majority of nurses experienced work fatigue in the moderate category,namely 37 nurses and nurses experienced fatigue in the high category as many as 30 nurses with good work scheduling. Inthe Somers'd test, the value (p = 0.009) or H0 was rejected and H1 was accepted, which means that there was a significantcorrelation between the two variables. Conclusion the work scheduler in the fairly good category has moderate and high workfatigue, while the very good work schedule has a moderate level of work fatigue, which tends to be low so that there is acorrelation between work scheduling and the work fatigue of inpatient nurses. Hospital is expected to apply work schedulingcharacteristics in arranging schedules in which one of the goals is to reduce the level of work fatigue of nurses who work inthe inpatient room of the Unisma Islamic Hospital Malang. Nurses are expected to reduce special requests for exchangingwork schedules with other nurses.